Three new species of the genus Odontomutilla Ashmead, 1899 (Hymenoptera: Mutillidae) from India - Terine, Joshua B.; Kumar, Girish P. (Zootaxa, 2024)
Three new species of velvet ant, Odontomutilla jaferpaloti sp. nov. (India: Karnataka), O. vishwanathi sp. nov. (India: Karnataka), and O. himalayensis sp. nov. (India: Uttarakhand), are described and illustrated. Diagnostic features of these new species, to separate them from similar species are provided. The updated key to the species of India is given.